PENGARUH PEMBERIAN ABU JANJANG KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA MEDIA GAMBUT - Fitry Ramanda, Rika; Setiawan, Beny; Wijaya, Andrix (Journal of Agro Plantation (JAP), 2022)
Oil palm (Elaeis guinensis Jacq) is a crop that is a top priority in plantations in Indonesia. Peat soil as a nursery medium faces many obstacles such as physical and chemical properties that are less supportive for plant growth. Oil palm janjang ash (AJKKS) is an ameliorant that can increase the uptake of macronutrients P, K, Ca and Mg so as to improve the physical and chemical properties of peat soil. This study aims to determine the effect of oil palm empty fruit bunch ash on the growth of oil palm seedlings on peat media. The study was conducted at the Ketapang State Polytechnic, from January to March 2022. This study used a non-factorial completely randomized design (CRD) consisting of 5 treatments and 6 replications. Treatment D0 (AJKKS 0 g/polybag), D1 (AJKKS 150 g/polybag), D2 (AJKKS 250 g/polybag) D3 (AJKKS 350 g/polybag) D4 (AJKKS 450 g/polybag). Parameters observed were peat soil pH, seedling height (cm), number of leaves (strands), stem diameter (mm), root volume (mL), and seedling dry weight (g). The provision of 450 g/polybag AJKKS had a significant effect on the growth of oil palm seedlings on peat soil pH, seedling height, number of leaves, stem diameter, root volume, and plant dry weight.